2019
DOI: 10.3389/fnins.2019.01002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Music in Families of Children With Hearing Loss and Normal Hearing in Australia, Finland, and the UK

Abstract: The primary aim of this current study was to compare the role, importance and value placed on music by families with normally hearing (NH) children, to those who had a child with a hearing loss (HL) who wore either hearing aids and/or cochlear implants. A secondary aim was to see whether this differed between the countries. Parents of children aged 2–6 years living in Australia, Finland, and the United Kingdom were invited to complete the Role of Music in Families Questionnaire (RMFQ). Two groups of participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…For these families, it may be that the expectations and beliefs about the benefits of music education for their children with ASD reflect how they feel about music more generally. This is in line with research examining musical engagement for children with hearing loss, in which families that valued and participated in music considered musical involvement for their children with hearing loss to be important (Driscoll et al, 2015; Looi et al, 2019). These families believed in music for music’s sake and, as such, expected that music education for their children would have the same outcomes that it does for any child: the chance to be musical.…”
Section: Resultssupporting
confidence: 85%
“…For these families, it may be that the expectations and beliefs about the benefits of music education for their children with ASD reflect how they feel about music more generally. This is in line with research examining musical engagement for children with hearing loss, in which families that valued and participated in music considered musical involvement for their children with hearing loss to be important (Driscoll et al, 2015; Looi et al, 2019). These families believed in music for music’s sake and, as such, expected that music education for their children would have the same outcomes that it does for any child: the chance to be musical.…”
Section: Resultssupporting
confidence: 85%
“…A combination of both generic and specific measures is recommended to fully comprehend the full extent of quality of life (Solans et al 2008;Warner-Czyz et al 2011). Formal Music Experience • The Role of Music in Families Questionnaire (RMFQ) was developed to evaluate the role of music in families of children with hearing loss, and their general attitudes and level of engagement with music (Looi et al 2018(Looi et al , 2019. One section of the RMFQ (Childhood Music Participation and Experiences) was used in the present study to appraise the level of formal music participation and experience each participant had received before commencement of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…However, perceptual skills generally have little bearing on music appreciation and enjoyment (Looi et al 2012). Furthermore, family attitudes and support appear to have a greater impact on music engagement than perceptual factors (Gfeller et al 2019;Looi et al 2019).…”
Section: The Rationale For Music As (Re)habilitationmentioning
confidence: 99%
“…Interventions involving rhythm or musical activities have the potential to enhance temporal attention, rhythmic aptitude, and foundational timekeeping capabilities, leading to improvements in language processing, reading proficiency, and the fundamental skills that support learning and literacy. Moreover, in the study by Looi et al (2018), cognitive and neural mechanisms play a role in the observed enhancements of language perception and auditory skills in children with cochlear implants. Schön and Tillmann (2015) also argued that processes such as spectrotemporal analysis, phonological awareness, implicit learning, syllabic processing, and speech segmentation affect these mechanisms and enhance language rehabilitation.…”
Section: Music's Benefits For Disabilities Of Language Developmentmentioning
confidence: 99%